Предмет: Алгебра,
автор: kalaydopulo
№6,7,помогите решить
Приложения:
Ответы
Автор ответа:
0
(2x-1)³=8x²(x-1)-4(x²+1)
8x³-3*4x²+3*2x*1-1=8x³-8x²-4x²-4
6x= -3 x= -0.5
9b²-16 (3b-4)(3b+4) 3b+4
----------------- = ------------------ = -------------
9b²-24b+16 (3b-4)² 3b-4
8x³-3*4x²+3*2x*1-1=8x³-8x²-4x²-4
6x= -3 x= -0.5
9b²-16 (3b-4)(3b+4) 3b+4
----------------- = ------------------ = -------------
9b²-24b+16 (3b-4)² 3b-4
Похожие вопросы
Предмет: Музыка,
автор: dashikkkOO
Предмет: Українська мова,
автор: Mefedrone1
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: Sashasashalop